2009
DOI: 10.1016/j.vetmic.2008.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and herd-level risk factors for intramammary infection with coagulase-negative staphylococci in Dutch dairy herds

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain.Page 1 making it the most frequently isolated grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
87
4
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(113 citation statements)
references
References 28 publications
17
87
4
5
Order By: Relevance
“…In contrast, Sampimon et al (2009) found increased odds for CNS IMI when cows had access to pasture in Dutch dairy herds. Other identified manageable herd-level risk factors included dry cows housed in one group instead of multiple groups, the use of non-tap water as a drinking source, and a high percentage of stalls contaminated with milk after milk leakage (Sampimon et al, 2009). In heifers, increased odds for CNS IMI were found in animals with a poor hygiene score, lack of teat dipping, and nonclipped udders before calving .…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…In contrast, Sampimon et al (2009) found increased odds for CNS IMI when cows had access to pasture in Dutch dairy herds. Other identified manageable herd-level risk factors included dry cows housed in one group instead of multiple groups, the use of non-tap water as a drinking source, and a high percentage of stalls contaminated with milk after milk leakage (Sampimon et al, 2009). In heifers, increased odds for CNS IMI were found in animals with a poor hygiene score, lack of teat dipping, and nonclipped udders before calving .…”
Section: Introductionmentioning
confidence: 72%
“…A lower CNS prevalence was observed in Canadian herds with sandor wood-based bedding products and in herds where cows had access to pasture (Dufour et al, 2012). In contrast, Sampimon et al (2009) found increased odds for CNS IMI when cows had access to pasture in Dutch dairy herds. Other identified manageable herd-level risk factors included dry cows housed in one group instead of multiple groups, the use of non-tap water as a drinking source, and a high percentage of stalls contaminated with milk after milk leakage (Sampimon et al, 2009).…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Unsuccessful treatments are usually observed for mastitis caused by beta-lactamase producing isolates, particularly S. aureus (Sol et al 2000). S. aureus is accepted as a major mastitis pathogen with laborious treatment, whereas CNS remains as a minor pathogen (Sampimon et al 2009). In many countries, CNS have become the most common mastitis-causing agents (Pyorala & Taponen 2009), and is proving to be as pathogenic as S. aureus, at least concerning the presence of antimicrobial resistance genes.…”
Section: Discussionmentioning
confidence: 99%
“…However, recently CNS have become a significantly predominant pathogen in bovine mastitis (Sampimon et al 2009, Kot et al 2012a. Similarly as S. aureus, CNS produce a number of virulence factors that determine the ability of adhesion, avoidance of host immune mechanisms, production of toxins and enzymes (Dinges et al 2000).…”
Section: Introductionmentioning
confidence: 99%